All Things Arabia : Arabian Identity and Material Culture - Baird, Ileana,; Yağcıoğlu, Hülya, (Arts and Archaeology of the Islamic World ;, 2021)
By employing the innovative lenses of thing theory and material culture studies, this collection brings together essays focused on the role played by Arabia's things from-cultural objects to commodities to historical and ethnographic artifacts to imaginary things-in creating an Arabian identity over time. The Arabian identity that we convey here comprises both a fabulous Arabia that has haunted the European imagination for the past three hundred years and a real Arabia that has had its unique history, culture, and traditions outside the Orientalized narratives of the West. All Things Arabia aims to dispel existing stereotypes and stimulate new thinking about an area whose patterns of trade and cosmopolitanism have pollinated the world with lasting myths, knowledge, and things of beauty.